Disasters, individuals, and communities: Can positive psychology contribute to community development after disaster?. Issue 1 (1st January 2020) - Morgado, Alice Murteira
ABSTRACT: Psychosocial responses to disasters at individual and community levels have been widely explored in the psychological and psychiatric literature. However, less attention has been drawn to the fields of positive, developmental, and community psychology. This paper focuses on conceptions of disaster, considering the extent of the impact based on disaster characteristics and consequences for the individuals and their communities. Research from positive, developmental, and community psychology is discussed, highlighting the role of personal and community resources. So far, existing literature has explored individual dimensions of trauma and outlined key mental health issues involved in exposure to disaster. Despite a variety of action-focused research, there is still need for increased awareness and acknowledgment of the interplay between community and individual resources in the outcomes of disaster response. As such, a conceptual model to understand factors related to disaster exposure and recovery is suggested, together with key recommendations for research and policy.